Solitude and modernity: Some reflections on Annette von Droste-Hülshoff’s poetry - Alba, Alessandro (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
Solitude and modernity: Some reflections on Annette von Droste-Hülshoff’s poetry. The text aims to an analysis of Droste’s poetry in consideration of the condition of the modern poet, who reflects upon himself’s loneliness. Far from being an individual, autobiographical condition, it is the basis for a consideration about general human’s condition, his social alienation which has made him/her incapable of feeling nature.